THE MEDIATING ROLE OF CO-PRODUCTION IN THE RELATIONSHIP BETWEEN INFORMATION TECHNOLOGIES AND SERVICE INNOVATION - Erdinç Koç; Seda Isgüzar (Enlightening Tourism: A Pathmaking Journal)
Service innovation has become increasingly important in recent years due to the competitive advantage it provides to companies operating in the service industry. Therefore, it is necessary to understand the factors that affect service innovation. In the few studies conducted on different sectors, the relationship between co-production and IT and service innovation has been tried to be tested separately. In this study, the mediating role of coproduction in the effect of information technologies on service innovation in the tourism sector has been investigated. In this way, it will contribute to the literature by investigating the effect of IT (directly and indirectly) and co-production (directly) on service innovation in the tourism sector. In the study data collected from 222 hotel managers were firstly subjected to validity and reliability analysis. Then, mediation analysis was applied within the scope of hypothesis tests. According to the results obtained, coproduction has a mediating role in this relationship. In the study, it was concluded that the IT capabilities of the hotels enable them to create service innovations through production together with online travel agencies.